2015
DOI: 10.1111/jon.12316
|View full text |Cite
|
Sign up to set email alerts
|

Charting Frontotemporal Dementia: From Genes to Networks

Abstract: Frontotemporal dementia (FTD) is a genetically and clinically heterogeneous syndrome that is characterized by overlapping clinical symptoms involving behavior, personality, language and/or motor functions and degeneration of the frontal and temporal lobes. The term frontotemporal lobar degeneration (FTLD) is used to describe the proteinopathies associated with clinical FTD. Emerging evidence from network-based neuroimaging studies, such as resting state functional MRI and diffusion tensor MRI studies, have imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 121 publications
(273 reference statements)
0
4
0
Order By: Relevance
“…FTD represents a group of disorders considered to be clinically and pathologically distinct from AD, although FTD may be mistaken for AD in the early clinical stages [10,11]. FTD clinically presents as either behavioural or aphasic variants, reflecting the topography of the underlying synaptic and neuronal loss [10,12,13]. The most common behavioural or frontal variant of FTD is associated with disinhibition, impulsivity, apathy, and loss of insight, which disturb social interaction, and it is typically accompanied by marked frontal lobe atrophy.…”
Section: Brief Overview Of Distinct and Overlapping Clinical Features...mentioning
confidence: 99%
“…FTD represents a group of disorders considered to be clinically and pathologically distinct from AD, although FTD may be mistaken for AD in the early clinical stages [10,11]. FTD clinically presents as either behavioural or aphasic variants, reflecting the topography of the underlying synaptic and neuronal loss [10,12,13]. The most common behavioural or frontal variant of FTD is associated with disinhibition, impulsivity, apathy, and loss of insight, which disturb social interaction, and it is typically accompanied by marked frontal lobe atrophy.…”
Section: Brief Overview Of Distinct and Overlapping Clinical Features...mentioning
confidence: 99%
“…(2) Genetics: Studies (e.g., Filippi, Agosta, & Ferraro, 2016;Kim et al, 2018;Loy et al, 2014) have indicated two categories of genes, i.e., deterministic genes and risk genes, can determine if an individual would develop dementia. For example, Cuccaro et al (2017) found Alzheimer's genes to be present in both 10.54392/ajir2221…”
Section: Introductionmentioning
confidence: 99%
“…The other brain disease, frontotemporal dementia (FTD), is clinically as well as a genetically syndrome of heterogeneous, which is featured by overlying clinical symptoms. These symptoms involve changes in behavior, language motor function, personality and degeneration of the brain region, frontal and temporal lobes [2]. FTD causes the cognitive and social decline of relative to the adult level of capability.…”
Section: Introductionmentioning
confidence: 99%